Developing a Software Application for the Study and Learning of Linear a Script - Mavridaki, Argyro; Galiotou, Eleni; Papakitsos, Evangelos C (Review of Computer Engineering Research, 2021)
The link between the scripts of many ancient languages and technology is minimum and occasionally superficial. As a result, their study and analysis remain a challenge for the researchers. Such an example of ancient script is Linear A, which is still considered the very first European script. Nowadays, there has been three main languages or language families of origin suggested, spoken in the Bronze Age, in order to attempt the decipherment of Linear A texts: (a) a language of the Aegean Sea, (b) certain languages of the Western Anatolia family and c) an Akkadian dialect. Therefore, there is a strong possibility that Linear A may render occasionally more than one language. The present survey initiates the adaptation of an existing computational framework for the interpretation and learning of syllabic scripts, already tested in Linear B script, to facilitate the research regarding the underlying language(s) of Linear A. Linear B have many signs in common with Linear A and of a known phonetic value per sign. Therefore, it is most appropriate for facilitating the study and potential decipherment of Linear A. This paper presents an outline of the designed software application, along with the sources that are studied and used for the adaptation of the existing computational framework for Linear B.